URGENSI MOTIVASI DALAM MENGHAFAL AL-QURAN DI MA’HAD TAHFIDZ AL-QURAN IHYAUL ULUM GRESIK - Ikhwanuddin, Muhammad (ILJ: Islamic Learning Journal, 2023)
Memorizing the Quran is a noble deed that requires seriousness and strong motivation where motivation plays an important role in encouraging students to continue to struggle and not give up in facing challenges during the memorization process. This study aims to examine the urgency of motivation in memorizing the Quran at Ma'had Tahfidz Al-Quran Ihyaul Ulum Gresik, as well as factors that can increase this motivation. The research is qualitative descriptive, with data collection methods of documentation, observation and interviews. The analysis is descriptive. The results showed that motivation plays an important role in the process of memorizing the Quran at Ma'had Tahfidz Al-Quran Ihyaul Ulum Gresik, including providing positive energy, encouraging discipline, overcoming boredom and laziness, and arousing enthusiasm. Factors that can increase motivation in memorizing the Quran include: 1) Giving motivation in class at every KBM, 2) Ascension exam every one Juz, 3) Examination for every five juz at the tasmi' and muraja'ah event, and 4) Support from parents.